Optimalisasi dalam Melafalkan Doa (Puja Tri Sandhya) Melalui Media Audio Visual bagi Siswa-Siswi Beragama Hindu di SD Negeri 6 Tanjung - Wirabhakti, I Ketut Chandra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Initial observations revealed that only two students were able to recite the prayer (Puja Tri Sandhya) optimally, while six other students were not able to recite the prayer (Puja Tri Sandhya) optimally. This can be expressed as 25% of students were able to recite the prayer (Puja Tri Sandhya) optimally, and 75% of students were not. This study aims to improve students' skills in reciting the prayer (Puja Tri Sandhya) using audio-visual media. The research type is qualitative descriptive. The data collection technique used in this study is observation. The purpose of the observation is to gather data about the learning process in the classroom. Data collected from observations are recorded on the provided observation sheets, then analyzed and presented in percentage (%). The results show that, after the actualization activity, seven students were able to recite the prayer (Puja Tri Sandhya) optimally, while only one student was not able to do so. This translates to 87.5% of students being able to recite the prayer (Puja Tri Sandhya) optimally, and 12.5% of students being able to recite some parts of the prayer (Puja Tri Sandhya).